SUBSTITUTED HETEROCYCLIC CHALCONES: ELECTROCHEMICAL, SPECTROSCOPIC AND THEORETICAL STUDY - Moreno, Yanko; Brovelli, Francisco; Ahumada, Guillermo (Journal of the Chilean Chemical Society, 2022)
We have studied the electronic and electrochemical properties of seven substituted heterocyclic chalcones (CHL 1-6) wich are functionalized with 2-thienyl groups. The phenyl ring of the chalcone scaffold has been substituted in orto or para position with electron donnor and acceptor groups (-F, -NO2, -CH3O). The electrochemical features were analyzed by cyclic voltammetry; irreversible processes were observed and attributed to the oxidation and reduction of the 2-thienyl group and the carbonyl group of the chalcone, respectively. DFT calculations were made to gain more in-depth understanding of their electronic properties. Relatively high HOMO level and low LUMO values were calculated, Eg values computed varies between 3.0-3.29 eV. These values enable us to postulate that these type of compounds are suitable building blocks to fabricate optoelectronic devices.